Anxiety Level, Interaction, and Family Harmony of Family Launching Stage in Bogor Regency and Bogor City - Wahyu Wulaningsih; Diah Krisnatuti (Journal of Family Sciences, 2019)
The family of the launching stage is a family when the children start leaving home. This research aims to analyze the effect of the level of anxiety and interaction into family harmony of launching stages in the regency and city of Bogor. Respondents in this study were wives from launching stage families with 60 respondents from regency areas and city areas. Respondents were selected for purposive sampling. Data was collected through interviews, then analyzed using descriptive analysis and inferential analysis. The results showed the anxiety level of wives is in the normal category. Family interaction in the middle category. Meanwhile, family harmony in a higher category. Overall, the length of the wife's education, the duration of her husband's education, per capita income, and family interaction had a significant positive relationship with family harmony and the level of anxiety had a significant negative relationship with family harmony. This study found that husband-wife interaction and parent-child interaction has a significant effect on family harmony.